Enzyme promiscuity of carbohydrate active enzymes and their applications in biocatalysis. (December 2020) - Pallister, Edward; Gray, Christopher J; Flitsch, Sabine L
Highlights: Carbohydrate-active enzymes (CAZymes) are invaluable tools for the synthesis of glycoconjugates. Manipulation of the glycosidic linkage (synthesis and hydrolysis) are particularly interesting. In addition, selective modifications such as oxidations and acylations are useful. CAZymes often display high reaction selectivity, but their substrate promiscuity can be exploited for in vitro applications. Abstract : The application of biocatalysis for the synthesis of glycans and glycoconjugates is a well-established and successful strategy, both for small and large scale synthesis. Compared to chemical synthesis, is has the advantage of high selectivity, but biocatalysis had been largely limited to natural glycans both in terms of reactivity and substrates. This review describes recent advances in exploiting enzyme promiscuity to expand the range of substrates and reactions that carbohydrate active enzymes (CAZymes) can catalyse. The main focus is on formation and hydrolysis of glycosidic linkages, including sugar kinases, reactions that are central to glycobiotechnology. In addition, biocatalysts that generate sugar analogues and modify carbohydrates, such as oxidases, transaminases and acylases are reviewed. As carbohydrate active enzymes become more accessible and protein engineering strategies become faster, the application of biocatalysis in the generation of a wide range of glycoconjugates, beyond natural structures is expected to expand.